Ke arah sistem perpustakaan digital bagi Perpustakaan Peta Negara, Jabatan Ukur dan Pemetaan Malaysia - Ng, Eng Guan; Ashaar, Mazlan; Awang Junidee, Dayang Norainie (Persatuan Pustakawan Malaysia, 2009)
Digitising library materials is now a neccesity and is an ejective way of channelling information to the masses. It is also a means of promoting the library and its services. The uniqueness of the library’s collection and the varied information needs of its users have spurred Perpustakaan Peta Negara (PPM, Jabatan Ukur dan Pemetaan Malaysia (JUPEM to provide online mapping and surveying information for easy access. In this paper; various recommendations and efforts of PPN 10 move towards digital library are explained. Similarly, the challenges and problems to set up a digital library at PPN as well as issues regarding information security which are necessary to safeguard web’are and sovereignity of a nation are also discussed.